المشكلات القانونية في تطبيق تعليمات حوكمة الشركات على العضو المستقل في مجلس إدارة الشركة المساهمة المدرجة في شركة بورصة عمان - الصنابرة، خالد علي عطية (مركز البحث وتطوير الموارد البشرية - رماح, 2020)
تناولت هذه الدراسة موضوع المشكلات القانونية في تطبيق تعليمات حوكمة الشركات على العضو المستقل في مجلس إدارة الشركة المساهمة المدرجة في شركة بورصة عمان، وقد هدفت هذه الدراسة إلى توضيح العقبات القانونية في تطبيق تعليمات حوكمة الشركات المساهمة المدرجة في شركة بورصة عمان لسنة 2017 على العضو المستقل في مجلس إدارتها، ووضع الحلول المناسبة لها. ومن خلال هذه الدراسة فقد توصل الباحث للعديد من النتائج والتي كان من أهمها ظهور العديد من العقبات فيما يتعلق بتطبيق قواعد الحوكمة على العضو المستقل، ومنها: عدم ذكر نسبة مساهمة العضو المستقل في الشركة الحليفة في تقرير مدقق حسابات الشركة، والتعارض في تحديد المصلحة للعضو المستقل والتي تنتفي معها صفة الاستقلالية في ذات تعليمات حوكمة الشركات المساهمة المدرجة في شركة بورصة عمان لسنة 2017، كما نصت المادة (4/ط) من تعليمات الحوكمة على إعطاء أعضاء مجلس الإدارة دورات تدريبية، ولكن لم يحدد المشرع أسس وشروط منح هذه الدورات. كما خرج الباحث بالعديد من التوصيات والتي من أهمها التأكيد على ضرورة استقلالية العضو المستقل في مجلس إدارة الشركة المساهمة المدرجة، والعمل على زيادة نسبة عدد الأعضاء المستقلين في مجلس إدارة الشركة المساهمة المدرجة والتخفيض من نسبة امتلاكهم للأسهم.
This study dealt with the issue of legal problems in implementing corporate governance instructions to the independent director (member) of the board of directors of the joint stock company listed on the Amman Stock Exchange and aimed at clarifying the legal obstacles in implementing the instructions of the corporate governance of the listed companies in the Amman Stock Exchange for 2017 to the independent director of the board of directors, and to develop appropriate solutions. Thus, the researcher used the analytical descriptive method to identify and analyze the legal problems in implementing of corporate governance instructions to the independent director and analyze them, and to dedicate the appropriate results from this study. Through this study, the researcher attained several results, the most significant of which are the emergence of many obstacles in applying the rules of governance to the independent director, including: Not mentioning the contribution percentage of the independent director in the affiliate company in the report of the company’s auditor, the Contradiction in determining the interest of the independent director, that eliminate of independence in the instructions of the corporate governance of the company listed in the Amman Stock Exchange for the year 2017. Article 4 (i) of the instructions of Governance stipulates that members of the Board of Directors should be given training courses, but the legislator did not specify the bases and conditions for giving these courses. The researcher also issued the most important recommendations, including the emphasis on the need for independence of the independent director of the board of directors of the listed company, to increasing the percentage of independent director members of the board of directors of the listed company, and to reduce how much they own shares.
Keywords: حوكمة الشركات -- البورصة العمانية -- الشركات التجارية -- الأوراق المالية